2010
DOI: 10.1002/jcp.22402
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of receptor activator of NFκB (RANK) in a series of primary solid tumors and related bone metastases

Abstract: Receptor activator of NFκB ligand (RANKL), RANK, and osteoprotegerin (OPG) represent the key regulators of bone metabolism both in normal and pathological conditions, including bone metastases. To our knowledge, no previous studies investigated and compared RANK expression in primary tumors and in bone metastases from the same patient. We retrospectively examined RANK expression by immunohistochemistry in 74 bone metastases tissues from solid tumors, mostly breast, colorectal, renal, lung, and prostate cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 16 publications
(19 reference statements)
7
91
0
4
Order By: Relevance
“…RANKL interacts with RANK and, in turn, recruits tumor necrosis factor receptor-associated factors (TRAFs) (27), leading to the activation of NF-κB, c-Jun N-terminal kinase (JNK), p38, ERK and Akt (28)(29)(30). Recent studies (4,(12)(13)(14)(15) have shown that RANK is also expressed on the surface of certain cancer cells and that RANKL functions as a chemokine and directs RANK-expressing cancer cells to preferentially migrate into bone, which is the crucial and initial step for bone metastasis. However, the manner in which this cytokine is involved in tumor metastasis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RANKL interacts with RANK and, in turn, recruits tumor necrosis factor receptor-associated factors (TRAFs) (27), leading to the activation of NF-κB, c-Jun N-terminal kinase (JNK), p38, ERK and Akt (28)(29)(30). Recent studies (4,(12)(13)(14)(15) have shown that RANK is also expressed on the surface of certain cancer cells and that RANKL functions as a chemokine and directs RANK-expressing cancer cells to preferentially migrate into bone, which is the crucial and initial step for bone metastasis. However, the manner in which this cytokine is involved in tumor metastasis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that RANKL binds to RANK or the decoy receptor osteoprotegrein (OPG) (5) to modulate osteoclast differentiation, activation and survival (6)(7)(8)(9)(10)(11). RANK is reportedly expressed in certain cancer cells, and the RANKL/RANK pathway induces the migration of prostate, renal, lung and human breast cancer cells, T47D (4,(12)(13)(14)(15). Furthermore, the RANKL/RANK pathway has been shown to trigger the bone-specific migration of RANK-expressing mouse malignant melanoma and human prostate cancer cells (4,13).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variations within the TNFRSF11B, RANK and RANKL genes have been widely studied not only for association with osteoporosis (Liu et al 2010, Roshandel et al 2010 but also with other disorders such as rheumatoid arthritis (Tan et al 2010), Paget's disease of bone (Whyte 2006), cardiovascular disease and cancer metastasis (Hanada et al 2011, Santini et al 2011. The RANK/RANKL/OPG system plays a very important role in the immune system cross-linking it to bone in what is known as osteoimmunology and evident in disorders such as rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…RANKL interacts with RANK and in turn recruits tumor necrosis factor receptor-associated factors (11) leading to activation of NF-κB, c-Jun N-terminal kinase, p38, ERK and Akt (12)(13)(14). As recently demonstrated, RANK has been found to be expressed in several solid tumors, such as breast cancer, prostate cancer, malignant bone tumors, multiple myeloma and squamous cell carcinoma (1,15), and RANKL directs RANK-expressing cancer cells to preferentially migrate into bone. However, the exact signaling pathways in tumor cell migration need to be elucidated.…”
Section: Discussionmentioning
confidence: 98%